2010
DOI: 10.1213/ane.0b013e3181d2732f
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Conduction Block in Isolated Toad Sciatic Nerve by Emulsified Isoflurane

Abstract: EI produced completely reversible and dose-dependent nerve conduction inhibition, which had slower onset and faster recovery compared with those produced by lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The toads were rapidly decapitated and killed [23], exposed both sides of the sciatic nerve lumbar plexus nerves to the legs of blunt isolated and immediately maintained in Ringer solution (RS). Fifty isolated toad sciatic nerves were selected and randomly assigned to 5 groups of 10 each: control group (RS), EOZ + Verapamil compound group (EOZ + Ver, 0.2% EOZ + Ver 0.05%), EOZ group (EOZ, 0.2%), verapamil group (Ver, 0.05%), and lidocaine group (Lid, 1% lidocaine).…”
Section: Methodsmentioning
confidence: 99%
“…The toads were rapidly decapitated and killed [23], exposed both sides of the sciatic nerve lumbar plexus nerves to the legs of blunt isolated and immediately maintained in Ringer solution (RS). Fifty isolated toad sciatic nerves were selected and randomly assigned to 5 groups of 10 each: control group (RS), EOZ + Verapamil compound group (EOZ + Ver, 0.2% EOZ + Ver 0.05%), EOZ group (EOZ, 0.2%), verapamil group (Ver, 0.05%), and lidocaine group (Lid, 1% lidocaine).…”
Section: Methodsmentioning
confidence: 99%
“…Emulsified isoflurane, mainly containing isoflurane and 30% intralipid, was prepared according to the well-established protocol developed by our laboratory. 4 Briefly, 8% (vol/vol) EI 100 mL contained pure liquid isoflurane 8 mL, and its relative density was about 1.05 g/mL. Isoflurane was supplied by Abbott Pharmaceutical Co Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies showed that emulsified isoflurane (EI) could produce epidural anesthesia in rabbits, 2 intravenous regional anesthesia (IVRA) in rat tails, 3 and conduction blockade in isolated sciatic nerve. 4 How these volatile anesthetics produce regional anesthesia remains unknown.…”
mentioning
confidence: 99%
“…Our previous studies found that in addition to its general anesthetic effect, EI produced regional anesthesia in various animal models [12][13][14][15] including IV regional anesthesia (IVRA) rat tails. 13 IVRA is a reliable technique, especially appropriate for operations on limbs.…”
mentioning
confidence: 99%